2012
DOI: 10.1111/j.1467-9507.2012.00659.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Religiosity, Family Resources and Stressors, and Parent–Child Attachment Security in Northern Ireland

Abstract: This study explores the associations between mothers' religiosity, and families' and children's functioning in a stratified random sample of 695 Catholic and Protestant mother-child dyads in socially deprived areas in Belfast, Northern Ireland, a region which has experienced centuries of sectarian conflict between Protestant Unionists and Catholics Nationalists. Findings based on mother and child surveys indicated that even in this context of historical political violence associated with religious affiliation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Another line of research in this project investigated the role of the family with a particular focus on religiosity, social coping, and father presence. Mothers’ religiosity—referring specifically to their adherence to Christianity, church attendance, and the centrality of religion in their lives—was consistently associated with better family functioning (Goeke‐Morey et al, 2013). Specifically, mothers’ religiosity related to more family cohesion and behavioral control, and less family conflict, psychological distress, and adjustment problems.…”
Section: History Of the Projectmentioning
confidence: 99%
“…Another line of research in this project investigated the role of the family with a particular focus on religiosity, social coping, and father presence. Mothers’ religiosity—referring specifically to their adherence to Christianity, church attendance, and the centrality of religion in their lives—was consistently associated with better family functioning (Goeke‐Morey et al, 2013). Specifically, mothers’ religiosity related to more family cohesion and behavioral control, and less family conflict, psychological distress, and adjustment problems.…”
Section: History Of the Projectmentioning
confidence: 99%
“… 48 Likewise, parents who were more available were likely to raise more religious and less violent adolescents. 23 Additionally, levels of maternal religiosity were associated with lower conflict and psychological distress at home, greater trust in the parent child relationship, 22 and desirable emotional and behavioural outcomes in adolescents. 49 …”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have indicated a protective role of religiosity in intimate partner violence (IPV), in fights and gang affiliations 18–21. Research also showed a potential protective role of religiosity on children when the parents were religious,22–24 which could be due to the moral and spiritual values shared within the home. Although the mechanisms are still not clear, R/S have an influence on violent outcomes, both in childhood and adulthood23 25 which, in other words, may explore R/S as a good candidate for mediation analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Since young children in particular are primarily exposed to religion within the context of their families, parent and family religious influences on young children have often been examined (Bader & Desmond, 2006;Goeke-Morey et al, 2013;Hair, Moore, Hadley, & Sidorowicz, 2008;Huesmann, Dubow, & Boxer, 2011;Jacobs et al, 2012;Kim, McCullough, & Cicchetti, 2009;Lustig et al, 2004;Petts, 2011;Vaaler, 2008). A variety of studies have found high correlations between parent religiosity and child religiosity, so that studying a parent's religiosity can provide some perspective on the child's religiosity as well (Bader & Desmond, 2006;Carothers Bert, 2011;Francis & Gibson, 1993;Huesmann et al, 2011;Jacobs et al, 2012;Leonard, Cook, Boyzatis, Kimball, & Flanagan, 2013;Okagaki & Bevis, 1999;Schreiber, 2013 Studies have also shown a direct relation between higher levels of parent religiosity or the religiosity of the family as a whole and lower levels of psychopathology in children (Caputo, 2004;Carothers Bert, 2011;Christian & Barbarin, 2001;Farmer, Sinha, & Gill, 2008;Goeke-Morey et al, 2013;Jacobs et al, 2012;Kim et al, 2009;Vaaler, 2008;van der Jagt-Jelsma et al, 2011). Parental religion is related to a variety of other family-level factors that could promote the resilience of the child.…”
Section: Child Versus Parent Religiositymentioning
confidence: 99%
“…This association holds even though the grandparents' religiosity no longer correlates with their own child's aggression at that later date. A study of families in Northern Ireland found that mothers' religiosity negatively correlated with child conflict, psychological distress, and adjustment problems(Goeke-Morey et al, 2013). These studies indicate that parental religiosity may indeed be related to children's psychological adjustment, but the means of measuring religiosity are still quite disparate.…”
mentioning
confidence: 99%